The effect of recovery methods and post-exercise rehydration fluids on heart rate and blood pressure - Risa Hadi; Harun Harun; Nur Khoiriyah (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2025)
The purpose of this study was to analyze the effects of various recovery methods and rehydration on heart rate and blood pressure. The 24 athletes (age 24,3±5,1 years, 67,6±16 kg, 166,5±5,2 cm, and VO2max 40,6±2,25 ml/kg/min) divided into six treatment groups, namely K1 (passive recovery), K2 (active recovery), K3 (isotonic fluids), K4 (green coconut water), K5 (active recovery+isotonic fluids), and K6 (active recovery+green coconut water). All subjects underwent a fatigue protocol using the Yoyo intermittent recovery test level 1 (YYIRT1), blood pressure and heart rate were measured pre and post the recovery intervention to assess the effects of various types of treatment. The results of this study indicate that active recovery, passive recovery, rehydration fluid administration, and their combination did not reduce systolic blood pressure (p>0.05). However, there was a significant difference in the reduction of diastolic blood pressure (p=0.045). The recovery method using isotonic fluids (K3) showed the highest reduction in diastolic pressure compared to the other treatments. The results of the difference test analysis show a significant difference in heart rate after treatment in each group (p=0.013). Similar results were also found for the difference value between treatments (p=0.004). This study show that the recovery method using isotonic fluids showed the highest reduction in diastolic pressure and heart rate after high intensity exercise compared to the other treatments. Active recovery method after exercise showed most significant decrease in heart rate after exercise.